Pelanggaran Distinction Principle dalam International Armed Conflict di Yaman Berdasarkan Hukum Humaniter Internasional - Magdalena, Try Intan Febrian (NOVUM : JURNAL HUKUM, 2020)
The international armed conflict in Yemen have occurred since 2010 until now involving the Houthis and the Yemeni Government and their coalition. This conflict has claimed many lives, many of whom are civilians. Meanwhile based on the distinction principle as stated in Article 48, Article 51 number 2, and Article 52 number 2 of Additional Protocol I 1977 states that parties to an armed conflict must distinguish between civilians and combatants and are prohibited from targeting civilians as attacks. This study aims to analyze and formulate what actions taken by the Houthis and the Yemeni Government in armed conflict in Yemen violate the distinction principle based on International Humanitarian Law. This research is a normative study using a statutory and conceptual approach and using descriptive analysis techniques. The results of the study and discussion stated that the Houthi Group and the Yemeni Government and their Coalition had violated the dictinction principle by conducting indiscriminate attacks through attacks on places that were filled with civilians, such as housing, markets and airports.